2017
DOI: 10.1080/24750573.2017.1343224
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of schizotypy on cannabis use predictors

Abstract: OBJECTIVES: In this study, it was aimed to compare male persons with cannabis abuse in terms of schizotypal features with a control group paired in age, sex, and education level, and to find a subgroup in the group of cannabis use whose schizotypal points are higher than those having personality disorder as an another factor increasing the tendency of cannabis use. METHODS: A total of 251 consequent male patients aged between 18 and 65 years with cannabis use disorder were admitted to the outpatient clinics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Consistent with this, we noted higher schizotypal scores in cases compared with controls, with elevated scores in the ‘odd beliefs and magical thinking,’ ‘unusual perceptual experience,’ and ‘odd and eccentric behavior’ subdomains. Several studies have observed a similar association between cannabis use and higher schizotypy scores, but many of these studies did not control for other drug/alcohol use (Skosnik et al ., 2008; Eren et al ., 2017). There is also some support for a causal influence of early cannabis exposure on later emergence of schizotypal symptoms during adulthood (Anglin et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, we noted higher schizotypal scores in cases compared with controls, with elevated scores in the ‘odd beliefs and magical thinking,’ ‘unusual perceptual experience,’ and ‘odd and eccentric behavior’ subdomains. Several studies have observed a similar association between cannabis use and higher schizotypy scores, but many of these studies did not control for other drug/alcohol use (Skosnik et al ., 2008; Eren et al ., 2017). There is also some support for a causal influence of early cannabis exposure on later emergence of schizotypal symptoms during adulthood (Anglin et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%